Automatic synthesis of self-clocked asynchronous state machines and parallel controllers - Aghdasi, Farhad (Zielona Góra: Uniwersytet Zielonogórski)
The classical methods for the design of asynchronous state machines are usually complicated due to critical races and hazards, and necessitate special state assignment techniques and hazard free combinational logic leading to extra hardware. The necessity for such special considerations prevents asynchronous designs to take advantage of the CAD tools developed for synchronous machines.
Keywords: sterowanie; sterowanie-teoria; sztuczna inteligencja; matematyka stosowana; informatyka